Nexus between Sportsmen Injuries and Economic Survival in Future Life - Wei Heyong; Su, Ying-Yueh; Wei, Siao-Yun; Talant Boleyev; Yen-Ku Kuo; Syed Zeeshan Zafar (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Movement is the essence of physical therapy. Due to the inherent nature of sports as a physical activity, they can often lead towards sport’s injuries and therefore may have a bearing on the economic aspects of the field or industry of sports. Athletes cannot resume at their previous level of activities if they fear re-injury or serious injuries. Competitive athletes have the highest injury rates (for example, adolescent elite athletes). Anterior cruciate ligament (ACL) injuries are the highest sport's injuries found in female players. Athletes might end their career prematurely by halting sport participation. The study's primary objective is to identify and discuss health variables, injury patterns, and training modes. These health variables include self-esteem, nutritional behavior, self-perceived stress, risk factors, and nutritional behavior in adolescent elite athletes. This is done with a view to developing effective target prevention for sport's injuries and understanding the risk factors, fear of injury, and incidence/prevalence of injury in adolescent elite athletes. The health consequences of injury are rising due to the lack of prospective injury registration. The paper has analyzed the nexus between sportsmen's injuries and economic survival in the future. The paper is based on three variables: Sportsmen Injuries, Economic Survival, and GDP-and-GDP growth rates. The collected data was analyzed using SPSS-26 software to describe the nexus between Sportsmen’s Injuries and Economic Survival. It was found that there's a significant impact of sportsmen’s injuries on economic survival and GDP-and-GDP Growth Rates.